Augmented Reality Authoring of Digital Twins: Design, Implementation and Evaluation in an Industry 4.0 Context - Begout, Pierre; Kubicki, Sébastien; Bricard, Emmanuel; Duval, Thierry (Frontiers in Virtual Reality, 2022)
This paper deals with Digital Twins (DTs) for Industry 4.0 factories, and their implementation in the context of a reconfigurable factory. This context implies a modification of the layout of the workstations during production, and thus requires a live update of the digital twins according to these modifications. We needed this update done by the operators directly on the workstations using an AR authoring tool. A literature review helped us to determine the criteria that a tool should fulfill in order to achieve this goal. The most important criteria are that the tool should be suitable for use by operators not trained in AR, that the learning curve should be short, and that it should be usable in a reconfigurable factory context. We created a DT containing all the necessary factory data and 3D models of the workstation interaction zones of a real assembly line. We then developed a tool enabling operators to match the DTs with their physical twin (PT) in AR, as well as to update their position in case of a reconfiguration. The experimentation we carried out confirms our analysis and shows us that it is possible to deploy a DT in a factory quite simply if the positioning of the DTs is done by direct manipulation (the 3D objects are co-located with the operator's hand) with the help of an AR display device.